PEDAGOGICAL FOUNDATIONS OF IMPROVING MEDIA LITERACY FOR PRIMARY SCHOOL STUDENTS - Khushbakov, Ismail Urolmakhamatovich (SCIENCE and SOCIETY, 2026)
This article examines the pedagogical foundations of improving media literacy for primary school students based on a systematic and comprehensive approach. The content and essence of media literacy, its structural components, as well as the didactic, methodological, and psychological aspects of its formation are highlighted on a scientific basis. In the digital information space, special attention is paid to the development of students’ competencies in conscious perception, analysis, critical evaluation of information, detection of false information, and compliance with information security.